Modified harmonic balance method for forced nonlinear vibration of beam on an elastic foundation. (February 2023) - Rahman, MD Saifur; Trishna, Tabassum Akter
A modified harmonic balance method has been presented and adopted for the nonlinear vibration problem of beams on an elastic foundation. By this method, a nonlinear algebraic equation along with a set of linear algebraic equations are required to be solved, which reduces computation effort. The results determined by the present method are compared with the corresponding results obtained by the existing method. Besides, the effect of various parameters on nonlinear vibrational behavior is examined.